REDUCING PATIENT ANXIETY UNDERGOING SURGERY THROUGH PROVIDING ANESTHESIA EDUCATION COUNSELING IN KEDIRI DISTRICT GENERAL HOSPITAL - Astutik, Reni Yuli; Wijaya, Windy Ari; Khomsiyatin, Binti Ratna (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Surgery is a medical procedure that can increase anxiety, making preoperative anxiety a common mental health issue experienced by many patients. This study aims to analyze changes of anesthesia education counseling intervention with leaflet in the premedication room on reducing anxiety in patients about to undergo surgery. Methods: This activity was carried out by providing anesthesia education counseling interventions carried out by anesthesiologists using leaflet media to patients before undergoing surgery. This activity began by measuring patient anxiety using the Hamilton Anxiety Rating Scale (HAM-A) questionnaire in 36 patients, then anesthesia education counseling interventions were given and patient anxiety was re-evaluated. Data were analyzed using the Stuart-Maxwell Test, with a significance level of ≤ 0.05. Results: Most respondents had anxiety levels above the mild category (mild to moderate-severe category) totaling 32 patients (94.4%). The majority of these patients fell into the mild to moderate category (16 patients, 44.4%), followed by moderate to severe (10 patients, 27.8%) and severe anxiety (8 patients, 22.2%). Only 2 patients (5.6%) experienced mild anxiety. After the anesthesia education counseling interventions, all respondents exhibited mild anxiety, totaling 36 patients (100%). The results of the Stuart-Maxwell test showed a p-value of 0.000, indicating a significant difference in the level of patient anxiety before and after the anasthesia education counseling intervention. Conclusion: Providing anesthesia education counseling intervention with leaflet in the premedication room has a significant effect on reducing anxiety in patients who will undergo surgery.